Relevansi Eklesiologi Communio Konsili Vatikan II Terhadap Hukum Kanonik 1983 - Yohanes Wilson Bei Lena Meo (Studia Philosophica et Theologica, 2020)
Communion, as expressed fully in Eucharist, for its bond with salvation, is the first and foremost obligation of every member of the faithful. This obligation arises from baptism, as a sacrament which incorporates the faithful into the mystical body of Christ and accompanies the faithful in all their action: the sacramental life, of faith and of relationship with ecclesiastical authority. The Second Vatican Council has placed communion as one of the important ecclesiological paradigms. The process of revision of Code of Canon Law itself is carried out in harmony with the ecclesiological paradigm of the Second Vatican Council. Counted among the visible elements of communion, Canon Law has tried also to translate the conception of communion into juridical language, which contains the rights and obligations of the faithful to endeavor and maintain it. This article has its purpose as an effort to see the relevance of the concept of communion in the Second Vatican Council to the Code of Canon Law promulgated in 1983.